Characterization of vacuum-deposited and solution-processed N, N′-bis-(1-naphthyl)-N, N′-diphenyl-1, 1′-biphenyl-4, 4′-diamine hole transport layers based organic light emitting devices - Nguyen, Huu Tuan; Duong, Anh Tuan; Lee, Soonil (Optical Materials, 2021)
We report the operation characteristics of green tris-(8-hydroxyquinoline)aluminium (Alq3) organic light emitting devices (OLEDs) with a N, N′-bis-(1-naphthyl)-N, N′-diphenyl-1, 1′-biphenyl-4, 4′-diamine (NPB) hole transport layer forming by either vacuum evaporation or solution processing. The maximum luminous yield of device having a vacuum-deposited NPB layer was 2.97 cdA-1 while that of device with solution-processed NPB layer was 2.56 cdA-1. To evaluate the operation characteristics of OLED devices, current densities with respect to bias voltages were investigated by using a modified Shockley equation. Similar behavior was obtained for ideality factors n in two types of devices suggesting the equivalent potential barriers and interface states for injection of holes from indium tin oxide anode to Alq3 emission layer. However, a lower parasitic series resistance (RS) and significant larger saturation current density (J0) were observed from the device with vacuum deposition method, which we attributed to a more dense and homogeneous NPB layer that is more favorable for hole current flow.
Keywords: Hole transport layers; Indium-tin-oxide anodes; Operation characteristic; Organic light-emitting devices; Parasitic series resistance; Saturation current densities; Tris(8-hydroxyquinoline); Vacuum deposition method; NPB HTL; OLEDs; Shockley equation; Solution processing; Vacuum deposition